Relationship between breastfeeding duration, lifestyle and obesity in children aged 3–16 years: a cross-sectional study - Liu, Yu; Gu, Yiyao; Mu, Jie; Duan, Zhi; Wang, Xixiang; Ren, Xiuwen; Liu, Lu; Xu, Jingjing; Zhang, Chi; Zhou, Shaobo; Ma, Ning; Yuan, Linhong; et al. (Frontiers in Nutrition, 2025)
IntroductionChildhood obesity is emerging as an increasingly severe public health problem. Effective lifestyle and dietary interventions are urgently needed to prevent childhood obesity. The study explored the association of breastfeeding duration in early life and lifestyle habits with childhood obesity.MethodsA total of 541 children aged 3–16 at Suzhou Science and Technology City Hospital were included in this analysis. The participants were categorized into obesity group and non-obesity group. Assigned and calculated the score of lifestyle habits and the total score of lifestyle habits and breastfeeding. Logistic regression was used to analyze the risk of obesity with breastfeeding and/or lifestyle habits scores, and ROC curves were applied to evaluate the accuracy of the models. SHapley Additive exPlanation (SHAP) was used to explore the specified impact of variables.Results(1) The dietary habits of children with obesity were marked by consuming more meat-based foods, preferring heavier flavors food items, and having a habit of snacking before meals. (2) It is recommended that newborn be breastfed for 4–12 months. (3) Healthy lifestyle habits and prolonged breastfeeding duration are both protective factors for childhood obesity respectively, and the synergistic impact is much more significant.DiscussionProlonging breastfeeding duration appropriately and cultivating healthy dietary habits might contribute to prevention of childhood obesity.